Biopolímeros sintetizados com mesocarpo de Attalea Speciosa Mart. ex Spreng e fibras vegetais - PAIXÃO, Louryval Coelho (2019)
Plastic materials are not always safe or environmentally friendly. Alternatively to these materials are biopolymers, which are polymers derived from living organisms or synthesized from renewable resources such as polysaccharides, proteins and lipids. These materials include babassu coconut mesocarp alginate, pectin and starch. Although these materials have promising application in the production of biopolymers, they are completely soluble in water, with high leaching tendency and low mechanical resistance. The combination of these and the use of plant fibers, such as fibers from the coconut of the bay-coconut and babassu coconut epicarp are being studied in this research, in order to improve the properties of these polymeric matrices, also considering the physical processes. and chemicals used in these fibers so that their dimensions are adequate and the fiber-to-matrix ratio is improved. Another important fact to study in the elaboration of biopolymers is the choice of plasticizers. In polysaccharides, for example, the most commonly used plasticizers are polyols (such as glycerol - G). These plasticizers make biopolymers more hydrophilic which may contribute to increase the water permeability and the susceptibility of the matrix to the humidity of the environment. Alternatively, hydrophobic plasticizers (such as tributyl citrate - CT) will help reduce this behavior. Thus, this work aims to elaborate and characterize sodium alginate biopolymers with different plasticizers and the use of coconut babassu pectin, alginate and mesocarp as base compounds with incorporation of natural plant fibers such as coconut-bay mesocarp and epicarp of babassu coconut in order to provide good mechanical, thermal, physical resistance and low leaching/solubilization tendency. The biopolymers were made according to the casting technique, in which a filmogenic solution was prepared and poured on a support, subsequently dried and stored at a relative humidity of 52%. G-plasticized alginate biopolymers were more hygroscopic than those with CT or CT / G mixtures. Plasticizer CT has made the water-soluble biopolymers with better mechanical properties. Sorption isotherms were well adjusted to the GAB model, with R2 close to 1 and low relative mean deviation. All biopolymers showed a single sharp Tg peak, showing higher values in the presence of CT. In the article of pectin with the fibers of the coconut from the bay of coconut, two experimental designs were applied for the treatment of the fibers (in natura fibers and chemically treated with 5% NaOH - m/m). The chemical treatment was efficient to partially remove hemicellulose and lignin from the fibers, with peaks reduction of ~ 1700 cm-1 related to these substances; the fibers caused more stable films to solubilization and leaching. Formulations with 9 g pectin/2 g fiber and 5 g pectin/0.5 g fiber were recommended as the selected conditions. Biopolymers formulated with 9 g of pectin/2 g of fibers showed the best results in tensile strength and elongation at break (2.35 MPa and 7.31%, respectively) for the treated fibers. In the mesocarp alginate article with babassu coconut epicarp fibers an experimental design of mixtures was applied, in which formulations 11 and 13 were selected. These formulations were subjected to a second cross-linking step which confirmed that the material had a low tendency to water absorption and compact and relatively homogeneous microstructure for fiber content. The best formulations have the potential to be applied to pilot tests and industrially produced.